Combination of Sturge-Weber syndrome and trigonocephaly - Ristow, Oliver; Freudlsperger, Christian; Berger, Moritz; Bächli, Heidi; Hoffmann, Jürgen; Engel, Michael (The journal of craniofacial surgery, 2016)
Regarded singly, both Sturge-Weber syndrome and trigonocephaly are rare congenital disorders. The cardinal features of Sturge-Weber syndrome are facial cutaneous capillary malformation (port-wine stain), leptomeningeal angiomatosis, and glaucoma. Premature closure of the metopic suture results in trigonocephaly. However, to the best of our knowledge, the diagnosis of a combination of both Sturge-Weber syndrome and trigonocephaly has not as yet been reported. This brief clinical study thus presents a patient with the unusual findings of a Sturge-Weber syndrome and simultaneous trigonocephaly induced by premature metopic synostosis. Thus, the rare combination of a port-wine stain involving the first division of the trigeminal nerve with the diagnosis of a craniosynostosis justifies the indication of a prophylactic magnetic resonance imaging acquisition before craniofacial surgeries, in order to prevent seizures and stroke-like episodes triggered by the surgical intervention.